Associação entre o sistema histo-sanguíneo ABO e mucosite oral - Luciene Della Libera, Miguel (2016)
Introduction: Oral mucositis is one of the most frequent diseases resulting from the side effects of Chemotherapy and Radiotherapy. In addition to compromising the quality of life, it increases the risk of infections, especially in patients undergoing bone marrow transplantation. However, genetic risk factors related to the susceptibility to this disease have not been fully clarified. Objectives: The aim of this study was to verify whether there is an association between ABO blood group phenotyping and oral mucositis. Methods: Data were selected from two hundred twenty nine records of patients undergoing HSCT in the Unit of Bone Marrow Transplantation of Hospital de Base São José do Rio Preto; out from the underlying disease between March 2006 and March 2012. Group 1 (G1) comprised data from patients with mucositis demonstrations after HSCT; Group 2 (G2) comprised patients without data mucositis demonstrations after HSCT. The Chi-Square and Fisher Exact tests were used for comparison of proportions between patients with and without oral mucositis and other risk factors. The mean of ages was calculated using the t test. The values of Odds Ratio (OR) and confidence intervals (CI) of 95% were also calculated (p <0.05). Results: No statistically significant differences were observed in the frequency of erythrocyte phenotypes of the ABO blood group in patients with and without oral mucositis (χ2: 2.654, p = 0.448, DF = 3). Statistically significant differences were found between the frequencies of the ABO blood group phenotypes when comparisons were related to the type of transplantation, conditioning and degree of oral mucositis. Conclusion: ABO blood group is not associated to the occurrence of oral mucositis in patients undergoing bone marrow transplantation.